Tonic vibration reflex in spasticity, Parkinson's disease, and normal subjects. Issue 4 (August 1972) - Burke, David; Andrews, Colin J.; Lance, James W.
Abstract : The tonic vibration reflex (TVR) has been studied in the quadriceps and triceps surae muscles of 34 spastic, 15 Parkinsonism, and 10 normal subjects. The TVR of spasticity develops rapidly, reaching a plateau level within 2-4 sec of the onset of vibration. The tonic contraction was often preceded by a phasic spike which appeared to be a vibration-induced equivalent of the tendon jerk. The initial phasic spike was usually followed by a silent period, and induced clonus in some patients. No correlation was found between the shape of the TVR and the site of the lesion in the central nervous system. The TVR of normal subjects and patients with Parkinsonism developed slowly, starting some seconds after the onset of vibration, and reaching a plateau level in 20-60 sec. A phasic spike was recorded occasionally in these subjects, but the subsequent tonic contraction followed the usual time course. Muscle stretch increased the quadriceps TVR of all subjects, including those with spasticity in whom the quadriceps stretch reflex decreased with increasing stretch. It is suggested that this difference between the tonic vibration reflex and the tonic stretch reflex arises from the selective activation of spindle primary endings by vibration, while both the primary and the secondary endings are responsive to muscle stretch. The TVR could be potentiated by reinforcement in some subjects. Potentiation outlasted the reinforcing manoeuvre, and was most apparent at short muscle lengths. As muscle stretch increased, thus producing a larger TVR, the degree of potentiation decreased. It is therefore suggested that the effects of reinforcement result at least partially from the activation of the fusimotor system. Since reinforcement potentiated the TVR of patients with spinal spasticity in whom a prominent clasp-knife phenomenon could be demonstrated, it is suggested that the effects of reinforcement are mediated by a descending pathway that traverses the anterior quadrant of the spinal cord.